Memory category according to the Russian and Tuvan languages - Arsenyeva, Irina A.; Pomortseva, Natalia V.; Kuular, Elena M.; Sheverinova, Olga V. (The New Research of Tuva, 2023)
The article is dedicated to delineating the most productive metaphorical models within the memory category and the linguistic modalities employed for its articulation in both Russian and Tuvan languages. The study is conducted within the theoretical framework of conceptual metaphor. The objective of the research is to ascertain the metaphorical models intrinsic to the memory category and to elucidate the linguistic mechanisms underpinning their expression in the Tuvan and Russian linguistic contexts. The focus of the investigation is directed towards lexical items, encompassing both individual words and phrases, that are utilized in the articulation of the memory category. Due to the absence of a dedicated term for “memory” in the Tuvan language, with semantically proximate substitutes such as “bash”, “ugaan”, “ugaan-bodal”, and “medel” (Russian equivalents: head, mind, intellect, consciousness), the nomenclature “category” is adopted herein to facilitate a comparative analysis of the mental lexicon pertaining to memory across the two languages. Despite their genetic dissimilarity and typological structural variance, these languages manifest ethnically specific characteristics in the conceptualization of the mental lexicon associated with memory among their respective speakers. The primary source material for this inquiry consists of lexicographic references. The narrative delineates diverse metaphorical models of memory and undertakes a comparative scrutiny of lexical expressions encapsulating these models in both Russian and Tuvan languages. Illustrative instances include the conceptualization of memory as a receptacle, as evidenced in Russian idioms like “derzhat’ v pamiati” and their Tuvan equivalents, such as “saktyp alyr” or colloquially “bashka tudar” signifying ‘to remember’ — literally translating to ‘to hold in the head’. Analogously, comparisons are drawn between Russian expressions like “ryt’sia v pamiati” and Tuvan phrases like “bash ishtin kaskannaar” conveying ‘to dig in the head’, among others. The concluding segment of the study synthesizes observations regarding ethnospecific idiosyncrasies inherent in the representation of the memory category. Instances include the conceptualization of memory as a vertical repository, elucidated through Russian linguistic constructs like “oselo v pamiati” (‘imprinted in memory’) and “vsplylo v pamiati” (‘surfaced in memory’). A parallel is drawn with Tuvan linguistic expressions such as “bash dydyk taar deg bolgan” or “bash üttüg-taar bolgan” signifying ‘memory has become damaged’ — literally denoting ‘head has become perforated like a canvas bag used for straining sour milk in making cottage cheese’.